Self compacting concrete from uncontrolled burning of rice husk and blended fine aggregate - Agus Setyo Muntohar, M.E. Rahman, dkk (ELSEVIER, 2014)
This paper presents an experimental study on the development of normal strength Self compacting concrete (SCC) from uncontrolled burning of rice husk ash (RHA) as a partial replacement to cement and blended fine aggregate whilst maintaining satisfactory properties of SCC. Experiments on the fresh and hardened state properties have been carried out on RHA based SCC from uncontrolled burning. The dosages of RHA are limited to 0%, 20%, 30% and 40% by mass of the total cementitious material in the concrete. The experiments on fresh state properties investigate the filling ability, the passing ability and the segregation resistance of concrete. The experiments on hardened state properties investigate the compressive and the splitting tensile strengths. The water absorption level of the concrete with changing RHA levels has also been monitored. The experimental studies indicate that RHA based SCC developed from uncontrolled burning has a significant potential for use when normal strength is desired.